Predictors of prolonged stay in the pediatric intensive care unit - Yudha Fadhol Arafah; Indah Kartika Murni; Desy Rusmawatiningtyas (Indonesian Pediatric Society, 2020)
Background Prolonged stay in the pediatric intensive care unit (PICU) reflects not only disease severity and patient health status, but also the performance and quality of patient care. Objective To to determine whether surgical procedure, severe malnourishment, cardiovascular condition, sepsis, and ventilator use were the predictors of prolonged PICU stay. Methods This nested, case-control study was conducted with secondary data from medical records of pediatric inpatients at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. We included pediatric patients aged 1 month-18 years treated in the PICU between 1 January - 31 December 2018. Predictors of prolonged stay were identified including surgical procedures, severe malnourishment, cardiovascular conditions, sepsis, and ventilator use. Logistic regression was used to identify independent predictors. Results Subjects' overall median age was 3.12 (IQR 0.76-18.8) years and the male to female ratio was 1:1. Median duration of ventilator use was 4 (IQR 1-21) days. The most common diagnosis was neurological disease (26.7%). Multivariate analysis showed that surgical procedure (OR 5.75; 95%CI 2.06 to 14.61) was statistically significant as an independent predictor of prolonged PICU stay. Conclusion Surgical procedure is the significant predictor of prolonged stay in PICU.